Photocatalytic decomposition of diclofenac potassium using silver-modified TiO(2) thin films - Cavalheiro, A. A. [UNESP]; Bruno, J. C. [UNESP]; Saeki, M. J. [UNESP]; Valente, J. P. S. [UNESP]; Florentino, A. O. [UNESP] (Elsevier B.V. Sa, 2008)
The effects of silver insertion on the TiO(2) photocatalytic activity for the degradation of diclofenac potassium were reported here. Techniques such as X-ray diffraction, scanning electron microscopy and UV-Vis spectroscopy were used to comprehend the relation between structure and properties of the silver-modified TiO(2), thin films obtained by the sol-gel method. The lattice parameters and the crystallinity of TiO(2) anatase phase were affected by inserted silver, and the film thickness increased about 4 nm for each 1 wt.% of silver inserted. The degradation of diclofenac potassium and by-products reached an efficiency of 4.6 mg(C) W(-1) when the material was modified with silver. Although the first step of degradation involves only the photochemical process related to the loss of the chlorine and hydrogen atoms. This cyclization reaction leads to the formation of intermediate, which degradation is facilitated by the modified material. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: silver; TiO(2); thin film; sol-gel; dip coating